Self-rated health as an indicator of ideal cardiovascular health among working-aged women - Veromaa V; Kautiainen H; Juonala M; Rantanen A; Korhonen PE (TAYLOR & FRANCIS LTD, 2022)
Objective: The aim of this study was to assess the relationship between self-rated health (SRH) and the American Heart Association's (AHA) concept of ideal cardiovascular health (CVH) among female municipal employees. Studies about the association are scarce, even though AHA recommends to use SRH status surveys in clinical practice and research settings of CVH.Design: Cross-sectional study conducted in 2014.Setting: SRH was assessed with a one-item question and the data of seven ideal CVH measurements (nonsmoking, body mass index <25.0 kg/m(2), healthy diet, physical activity at goal, blood pressure <120/80 mmHg, cholesterol <5.18 mmol/l and glucose (HbA1c < 6.0%)) was gathered with a physical examination, laboratory tests, medical history and self-administrated questionnaires.Subjects: A total of 725 female subjects from 10 work units of the city of Pori, Finland.Main outcome measures: SRH and ideal CVH.Results: Of the study subjects, 28.8% reported ill-health (poor/fair SRH). The sum of ideal CVH metrics was positively associated with good SRH driven by favorable health behaviors (nonsmoking, normal body mass index, healthy diet and physical activity). A linear decrease in the prevalence of 0-2 ideal CVH metrics, and a linear increase in 5-7 metrics was associated with better SRH. Nonsmoking and normal weight were the most potent indicators of good SRH in multivariate analysis.Conclusions: Most of the subjects with 0-3 of the seven CVH metrics at ideal level were dissatisfied with their health. Since unhealthy lifestyle factors accumulate mainly to people feeling ill-health, the value of SRH is worth recognizing especially in primary health care.